Congenital malaria in a European country. (12th December 2012) - Prior, Ana Rita; Prata, Filipa; Mouzinho, Ana; Marques, José Gonçalo
Abstract : A newborn of 26 days, born in Lisbon, Portugal, presented with fever, anaemia and thrombocytopaenia. She was admitted considering neonatal sepsis, but Plasmodium vivax was identified in the second peripheral blood smear performed. Parenteral quinine was started with good evolution. Despite clinicians' unfamiliarity with congenital malaria in non-endemic areas, this diagnosis, although rare, should not be forgotten in the evaluation of newborns/infants born to women from endemic areas or with recent trip to these areas.